AN INNOVATIVE TEACHER PROFESSIONAL DEVELOPMENT FOR LEARNING MANAGEMENT PROMOTING ENVIRONMENTAL SCIENCE LITERACY - Kijkuakul, Sirinapa; ฺBongkotphet Thitiya (Journal of Education and Innovation, 2024)
This is a multi-phase mixed-method study that aimed to build an innovation for teacher development in learning management that promoted scientific literacy within environmental contexts by 1) exploring teaching and learning situations among 346 teachers in Thailand’s Lower North region and then 2) developing the innovation through a collaborative effort involving six teachers and educational personnel. Also, the research included: 3) studying a way of transferring knowledge and experience from the innovation to 117 teachers; and 4) monitoring 12 voluntary teachers’ implementation of the innovation. Research instruments include an online survey, a focus group interview, a workshop evaluation, participant observations, reflective journals, and lesson plans. Mean, percentages, standard deviation, content analysis, and triangulations were used to analyze data, and these indicated that, firstly, their teaching goals incompletely covered scientific literacy, and most of them (>50%) had not had professional development about the literacy. Second, the innovation covers the online workshop with teaching demonstrations that integrate ideas about the Technological Pedagogical Content Knowledge (TPACK) and competencies based on the PISA’s scientific literacy. The innovation is at the highest appropriate level, according to experts’ evaluations. Consequently, the innovative transformation appeared through the online platform, Zoom Meetings, for four days, and the teachers expressed their satisfaction at the highest level of evaluation. Fourth, seventy-five percent of the volunteers adapted the innovation, i.e., learning activities, for their authentic classrooms. Finally, the research recommended further study of the scientific literacy of pre- and in-service teachers to enhance educational quality in science.